Virtual world experimentation: An exploratory study - Thomas Chesney; Swee-Hoon Chuah; Robert Hoffmann (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2007)
We explore the scientific potential of virtual worlds for experimental economists. In particular, we report the results of a series of virtual world experiments designed to examine the suitability of (a) users as subjects and (b) the computer interface as an experimental platform. Formal results and informal observations from the sessions are discussed in terms of the methodological opportunities and challenges of virtual experimentation generally.
Keywords: C72; C88; C99; Z13; 330; virtual worlds; laboratory experiments; human values survey; Wissenschaftliche Methode; Virtuelle Realität; Test; Sozialwissenschaft